Zoonotic intestinal nematodes in dogs from public parks in Yucatán, México - Rodrigo Adán Medina-Pinto; Roger Iván Rodríguez-Vivas; Manuel Emilio Bolio-González (Biomédica: revista del Instituto Nacional de Salud, 2018)
Introduction: Dogs represent a potential public health risk because of the natural transmission of zoonotic parasitic infections. Objective: To estimate the frequency and to determine factors associated with the presence of intestinal nematode eggs in dog feces collected in public parks of Mérida,Yucatán, México. Materials and methods: A total of 100 dog fecal samples collected from 20 public parks in two areas of Mérida were analyzed. Samples were processed by the centrifugation-flotation and the McMaster techniques to confirm the presence and to quantify the excretion of intestinal nematode eggs per gram of feces. The factors associated with the presence of nematode eggs were identified using the chi square univariate analysis. Results: We found an 11% frequency of fecal samples positive for intestinal nematode eggs. Eggs of three species of parasites were identified: Ancylostoma caninum was the most common (10%), followed by Toxocara canis (10%), and Trichuris vulpis (1%). Most positive samples were infected with only one intestinal nematode (10%), and only 1 % was positive for a mixed infection by A. caninum and T. vulpis. The presence of stray dogs in public parks was an associated factor (p=0.046) with a higher number of fecal samples positive for intestinal nematode eggs. Conclusions: The frequency of intestinal nematodes in dog feces with zoonotic potential was high in parks of Mérida, Yucatán, México; samples from parks where there were stray dogs had a higher possibility of being positive.